2011
DOI: 10.1016/j.ijnurstu.2010.10.005
|View full text |Cite
|
Sign up to set email alerts
|

Combining qualitative and quantitative research within mixed method research designs: A methodological review

Abstract: A trend for conducting parallel data analysis on quantitative and qualitative data in mixed methods healthcare research has been identified in the studies included in this review. Using triangulation as a methodological metaphor can facilitate the integration of qualitative and quantitative findings, help researchers to clarify their theoretical propositions and the basis of their results. This can offer a better understanding of the links between theory and empirical findings, challenge theoretical assumption… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
320
0
15

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 468 publications
(361 citation statements)
references
References 34 publications
4
320
0
15
Order By: Relevance
“…This retrospective study assessed participant"s behaviour at pre-pregnancy and during pregnancy. This approach provides an accurate description of human behaviour (32) especially in health research (33) , with the qualitative data providing meaning and explanation of the quantitative data.…”
Section: Methodsologymentioning
confidence: 99%
See 1 more Smart Citation
“…This retrospective study assessed participant"s behaviour at pre-pregnancy and during pregnancy. This approach provides an accurate description of human behaviour (32) especially in health research (33) , with the qualitative data providing meaning and explanation of the quantitative data.…”
Section: Methodsologymentioning
confidence: 99%
“…More specifically, 35 per cent of Australian women of child-bearing age (ages [25][26][27][28][29][30][31][32][33][34][35] are overweight or obese (9) .…”
Section: Introductionmentioning
confidence: 99%
“…However, as we only had self-reported measures of fidelity and session duration, we used the more general term, with a meaning more akin to "implementation effectiveness," which concerns participants' aggregate use [23]. To enhance understanding and explore features not captured by this model, a parallel qualitative analysis used group interviews [24]. Study method and reported findings adhere to components of the STROBE Statement for observational studies [25].…”
Section: Observational Studymentioning
confidence: 99%
“…It may be thought that the size of the sample is small, but in qualitative studies this usually is small, and the sample size was given by the saturation of the data, and was similar to that of other studies of the same subject [10,11].…”
Section: Limitations Of the Studymentioning
confidence: 89%